Perancangan Desain Antar Muka Sistem Informasi Pengarsipan Pada CV. Inti Jember Sukses - Doni Damara; Okta Veza; Indah Kusuma Dewi; Albertus Laurensius Setyabudhi; Muhammad Bobbi Kurniawan Nasution (Engineering and Technology International Journal, 2022)
This study aims to design and implement an archival information system at CV. Inti Jembar Sukses which can be used to manage transaction records and provide technological insights to leaders and staff who previously did not use information system technology with the system design stages using the waterfall method with five stages, namely needs analysis, system interface design. While the modeling used is the Unified Modeling Language (UML). Archive information system on CV. The core of jember success. The results of this study resulted in analysis, system interface design with UML modeling to create a system that can be used as an archive data manager and smooth access to company information that has resulted in the design that has been made. Archive information design on the CV. Inti Jembar Sukses where there are still several letter documents that have not been made due to time constraints and the design requirements are made online starting from the status of the archives and bidding documents.